Surfactant enhanced l-α-glycerylphosphorylcholine production from phosphatidylcholine using phospholipase A1 in the aqueous phase. Issue 5 (3rd September 2019) - Lu, Yuanyuan; Zhang, Alei; Wang, Xin; Hao, Ning; Chen, Kequan; Ouyang, Pingkai
Abstract: Enzymatic production of L-α-glycerylphosphorylcholine (L-α-GPC) is difficult due to the limited solubility of phosphatidylcholine (PC) in the aqueous phase. Surfactants can be used to improve the solubility and the dispersibility of non-polar chemicals in the aqueous media. In this study, various surfactants were investigated to improve L-α-GPC enzymatic production using phospholipase A1 (PLA1 ) in the aqueous phase. The results showed that Tween 20 was the most effective surfactant for enhancing L-α-GPC concentration. With 20 g . L −1 of Tween 20, the optimal conditions of PC hydrolysis were determined to be enzyme loading of 0.64 g . L −1 and substrate concentration of 60 g . L −1 at 45 °C for 1 h. In addition, the fed-batch catalytic process of PC was conducted to avoid substrate inhibition and increase product accumulation, resulting in 112.56 g . L −1 of L-α-GPC from 360.00 g . L −1 PC with yield of 91.36% within 3 h.